Avaliação qualitativa do efeito de histereses entre vazão e concentração de sedimentos em suspensão no rio Jundiaí, SP - Bermúdez, Luis Fernando Murillo; Martin, André Luís Sotero Salustiano (International Workshop for Innovation in Safe Drinking Water, 2022)
Hydrosedimentological dynamics in watersheds show a non-linearity and the factors that intervene are still the subject of debate in the scientific context. The present work, through qualitative analysis of the hysteresis effect between measured flow data and suspended sediment concentration data correlated with turbidity values, sought to preliminarily evaluate some of the variables that interfere in the sediment transport process. As a result, a description of 17 rainfall events was obtained for high flows where the predominance was of type eight, related to events with multiple discharge peaks that connect different sources of sediments upstream of the measurement point, generating patterns with greater complexity.